2018
DOI: 10.1017/s2045796018000732
|View full text |Cite|
|
Sign up to set email alerts
|

The same or different psychiatrists for in- and out-patient treatment? A multi-country natural experiment

Abstract: Aims A core question in the debate about how to organise mental healthcare is whether in- and out-patient treatment should be provided by the same (personal continuity) or different psychiatrists (specialisation). The controversial debate drives costly organisational changes in several European countries, which have gone in opposing directions. The existing evidence is based on small and low-quality studies which tend to favour whatever the new experimental organisation is. We compared 1-year clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Our qualitative study is of unique value by complementing the quantitative exploration where no significant differences between PCC and SC were found in terms of patient outcomes over a 1-year period [12]. It identifies and highlights substantial differences in terms of perceived advantages and shortcomings of both approaches.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our qualitative study is of unique value by complementing the quantitative exploration where no significant differences between PCC and SC were found in terms of patient outcomes over a 1-year period [12]. It identifies and highlights substantial differences in terms of perceived advantages and shortcomings of both approaches.…”
Section: Discussionmentioning
confidence: 88%
“…Advantages as much as disadvantages of both approaches may balance or counterweight each other resulting in similar primary outcomes in the quantitative follow-up, as specific aspects of care may have different relevance in specific contexts and logistic and organisational considerations may favour one approach over the other. Therefore, even though there appears to be no quantitative differences in primary outcomes between personal continuity and specialisation of care [12], the issue remains important for many clinicians and patients and influences their experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sanatinia et al (2016) found that frequent staff changes resulted in reduced patient satisfaction with care and a reduced quality of care provided. Conversely, Giacco et al (2018) found that there was no difference in patient outcomes over a period of 1 year between those treated under a specialization or COC system. Thus, they concluded that rather than focusing on the model in which care is provided; a greater focus needs to be placed upon the quality of the therapeutic relationships.…”
Section: Introductionmentioning
confidence: 88%
“…Giacco et al . () when comparing 1‐year clinical outcomes of the integrated and functional models in routine care across five European countries found no substantial impact on patient outcomes. However, Bird et al .…”
Section: Continuity Of Care Across Inpatient and Community Services: mentioning
confidence: 93%